2019
DOI: 10.1590/fst.30416
|View full text |Cite
|
Sign up to set email alerts
|

Gluten-free cookies elaborated with buckwheat flour, millet flour and chia seeds

Abstract: This study aimed to elaborate gluten-free cookies with buckwheat flour, millet flour, and chia seeds, using an experimental design to prepare cookies with texture and physical characteristics similar to those produced with wheat flour. 2 Material and methods 2.1 Material Wheat (Triticum aestivum L.) flour, chia (Salvia hispanica L.) seeds, hulled millet (Panicum miliaceum) grains and the other ingredients used in the formulations were purchased commercially in Campinas-SP. Buckwheat (Fagopyrum spp) grains were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 30 publications
0
27
1
1
Order By: Relevance
“…That may be solved using other types of flour combined ( Lovis, 2003 ; Rai & et al., 2014 ), added to other protein or starchy ingredients, in order to adjust the particular characteristics in the desired formulation ( Mancebo et al., 2016 ). Replacements with rice ( Chung et al., 2014 ), maize ( Korus et al., 2017 ), pseudocereals such as quinoa ( Alencar et al., 2017 ; Kahlon et al., 2016 ), amaranth ( Alencar et al., 2015 ; De La Barca et al., 2010 ), buckwheat and millet ( Brites et al, 2019 ), or even pulses such as beans ( Sharma et al., 2017 ), chickpeas ( Oauzib et al., 2016 ), lentils ( Morales et al., 2015 ; Zucoo et al., 2011 ) and broad beans ( Abou-Zaid et al., 2011 ) flours, among many others studied by the industry, have contributed to update knowledge, products and consumption patterns among people who need and desire new food options.…”
Section: Introductionmentioning
confidence: 99%
“…That may be solved using other types of flour combined ( Lovis, 2003 ; Rai & et al., 2014 ), added to other protein or starchy ingredients, in order to adjust the particular characteristics in the desired formulation ( Mancebo et al., 2016 ). Replacements with rice ( Chung et al., 2014 ), maize ( Korus et al., 2017 ), pseudocereals such as quinoa ( Alencar et al., 2017 ; Kahlon et al., 2016 ), amaranth ( Alencar et al., 2015 ; De La Barca et al., 2010 ), buckwheat and millet ( Brites et al, 2019 ), or even pulses such as beans ( Sharma et al., 2017 ), chickpeas ( Oauzib et al., 2016 ), lentils ( Morales et al., 2015 ; Zucoo et al., 2011 ) and broad beans ( Abou-Zaid et al., 2011 ) flours, among many others studied by the industry, have contributed to update knowledge, products and consumption patterns among people who need and desire new food options.…”
Section: Introductionmentioning
confidence: 99%
“…These results were consistent with those observed by Dachana et al [62], which stated that a thin sheet representing the protein matrix, along with small and large embedded starch granules, can be observed in cookie dough. The starch granules, which were almost entirely covered by thin layers of protein film, were melted and re-solidified fat [63]. It can be seen in Figure 3b that the area covered with the protein matrix is larger than that shown in Figure 3a.…”
Section: Effect Of Factors On Stickinessmentioning
confidence: 89%
“…The highest content of crude ash (3.85%) was observed in cookies with 20% red currant pomace flour and the lowest (1.56%) in the wheat flour cookies. Brites et al (2019) reported that content of crude ash in wheat flour cookies is 0.51%.…”
Section: Cookies Analysismentioning
confidence: 99%